Quantifying Differences in Swedish Take-Private Transactions : Strategic vs. Financial Buyers - Ziernwald, Karel; Svačina, Pavel, 1979-; Arlt, Josef, 1962-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis investigates the determinants of acquisition premiums in Swedish public tender offers between 2000 and 2025, a period characterized by exceptional private equity density and capital saturation. Using multivariate OLS regression on a dataset of 550 transactions from Nasdaq Stockholm, the study analyzes whether the pressure of record “dry powder” has eroded financial sponsors’ pricing discipline. The results confirm that financial acquirers pay systematically lower premiums (approx. 7.4%) than strategic buyers, though this discount is narrower than global benchmarks, suggesting that intense competition is compressing the valuation spread. Furthermore, contrary to standard theory, hostile bids trade at a discount (-8.6%) due to the strict neutrality rule, and regulated Main Market targets command lower premiums than First North Market, suggesting higher pre-bid pricing efficiency.
Vedoucí práce: Pavel Svačina
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses